The Influence of Using Ambonese Malay Language on Learning of Indonesian Language of Students at PAUD Sinar Terang Anak Bangsa - Marlen Wariunsora (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
Teachers and students use Ambonese Malay in learning Indonesian because learning a second language is inseparable from knowledge of the first language mastered by early childhood. This study aims to determine the effect of using Ambonese Malay on Indonesian language learning in early childhood education. This research is a sociolinguistic study to describe the phenomenon of language use. This study's results indicate three influences of the use of Ambonese Malay on students' learning of Indonesian. First, Ambonese Malay has a role as a 'language transfer tool' for children learning to understand a second language, namely Indonesian. Second, it is easy for the teacher to teach Indonesian to children because they can use Ambonese Malay vocabulary as the language of instruction to help students understand what the teacher means by learning Indonesian. Third, students gain knowledge of Indonesian vocabulary through the Ambonese Malay used by students and teachers in class.